2008
DOI: 10.1111/j.1558-5646.2008.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EVOLUTION OF REPEATED MATING IN THE BURYING BEETLE,NICROPHORUS VESPILLOIDES

Abstract: Animals of many species accept or solicit recurring copulations with the same partner; i.e., show repeated mating. An evolutionary explanation for this excess requires that the advantages of repeated mating outweigh the costs, and that behavioral components of repeated mating are genetically influenced. There can be benefits of repeated mating for males when there is competition for fertilizations or where the opportunities for inseminating additional mates are rare or unpredictable. The benefits to females ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 72 publications
8
64
1
Order By: Relevance
“…In apparent support of this criticism, a range of studies have failed to find a positive genetic correlation between male and female mating speed or mating frequency in chicken (20), Drosophila (21), stalk-eyed flies (22), and bean beetles (23). Only one study on mating frequency in burying beetles (24) has found a strong between-sex genetic correlation, although mating frequency was measured here with the same partner rather than with different partners.…”
Section: Discussionmentioning
confidence: 85%
“…In apparent support of this criticism, a range of studies have failed to find a positive genetic correlation between male and female mating speed or mating frequency in chicken (20), Drosophila (21), stalk-eyed flies (22), and bean beetles (23). Only one study on mating frequency in burying beetles (24) has found a strong between-sex genetic correlation, although mating frequency was measured here with the same partner rather than with different partners.…”
Section: Discussionmentioning
confidence: 85%
“…We did not manipulate copulation number independently of mate number; however, we know that repeated mating (i.e. several matings with the same male) does not improve any measure of offspring fitness [32]. Thus, because of our previous studies, we were confident that any effect of polyandry would not be confounded with numbers of matings.…”
Section: (A) Experimental Animalsmentioning
confidence: 99%
“…Our previous work shows that for the single male treatment, it is necessary for females to mate more than once to obtain full fertility [32]. Thus, these females were enclosed with their mate for 50 min, during which time a pair copulates three times or more.…”
Section: (A) Experimental Animalsmentioning
confidence: 99%
See 2 more Smart Citations